Fabrication and characterization of the porous titanium alloy by argon filled pore expansion technique - Nugroho, A.; Leadbeater, Garry; Davies, Ian (2018)
© Published under licence by IOP Publishing Ltd. The characterization of fabricated porous ß titanium alloy using powder metallurgy technique from elemental powders, i.e. Ti, Nb, Ta and Zr has been carried out. Those elemental powders were blended and filled in steel container. The container was vacuumed and pressurized with argon gas subsequently. The pressurized container was subjected for hot isostatic pressing (HIP-ing) at temperature of 1100°C under 100 MPa of argon pressure subsequent furnace cooling. The HIP-ed container was cut into cubic shape followed by placing in vacuum furnace at high temperatures of 1100°C and 1125°C for foaming process. While microstructure and hardness examination by electron microscope and Vickers indentation were respectively conducted, chemical composition of the porous alloy was determined using X-ray fluorescence (XRF). Their corrosion behavior was evaluated by using potentiodynamic polarization technique. The result shows that whilst the porosity level and the hardness increased with the increase of foaming temperature, the specimen foamed at the lower temperature exhibited higher pitting and corrosion resistance.